Teacher modes of adaptation to innovations in social studies - Malicdem, Melanio Doria 1936-
This study aims to determine the teacher modes of adaptation to innovations in the secondary social studies education; to appraise the influence of social acceptance values to such modes of adaptation; to assess the teacher's facilitative characteristics towards the said innovations; to compare the modes of adaptation of public and private secondary teachers, their acceptance values and facilitative characteristics; and to analyze the intercorrelations of the three variables used.